2014
DOI: 10.2478/s13382-014-0313-5
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after coronary revascularization procedures and a patient’s job satisfaction: A prospective study

Abstract: Objectives: Research into work reintegration following invasive cardiac procedures is limited. The aim of this prospective study was to explore predictors of job satisfaction among cardiac patients who have returned to work after cardiac rehabilitation (CR). Material and Methods: The study population consisted of 90 cardiac patients who have recently been treated with coronary angioplasty or heart surgery. They were evaluated during their CR and 12 months after the discharge using validated self-report questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Regarding the physiological indicators of health or illness, our results show that higher psychological job demand is linked to more risk for sickness absence [ 73 ], less job satisfaction [ 65 , 74 ] (mainly, with a full RTW [ 83 ]), and a deterioration in the quality of the work experience [ 66 ]. Nevertheless, work modifications during the return-to-work process reduce physiological symptoms and increase job satisfaction, especially in the case of women [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the physiological indicators of health or illness, our results show that higher psychological job demand is linked to more risk for sickness absence [ 73 ], less job satisfaction [ 65 , 74 ] (mainly, with a full RTW [ 83 ]), and a deterioration in the quality of the work experience [ 66 ]. Nevertheless, work modifications during the return-to-work process reduce physiological symptoms and increase job satisfaction, especially in the case of women [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most used are the Center for Epidemiologic Studies Depression Scale (CESD) [ 28 , 69 ] and the Brief Job Stress Questionnaire [ 65 , 73 ]. It should also be mentioned that Abegglen et al [ 62 ] and Gragnano et al [ 83 ] presented two recently developed scales: The Work and Health Questionnaire and the Work–Health Balance Questionnaire (WHBq). The former identifies workers at risk of a complicated recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…As 14% of our population did not return to work following an AMI, these factors may provide worthwhile targets for future interventions to improving AMI patients’ resumption to work and may promote effective communication between physicians and patients. For example, more support may be required for patients in manual or semi-skilled labor roles (which may require intense physical activity) 26, 27 and/or these patients may not have the education or training to seek alterative work in clerical or professional roles. 28 In addition, cardiac rehabilitation or home healthcare which seeks to improve the quality of life of patients, including providing more social supports, may be worthwhile targets for intervention as 63% of those not retuning to work following AMI reported that they were no longer able to work, perhaps due to deteriorating health.…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly due to next factors. Firstly, the inability of patients to coordinate the relationship between treatment and work (33). As the work performance of these patients generally could not reach the pre-MI state, some of them worried whether they could continue to enjoy equal workplace-related rights.…”
Section: Discussionmentioning
confidence: 99%